School physical education and health based on the principles of body literacy: propositions and validation of an educational technology - Evelyne Ferreira de Castro; Magna Leilane da Silva; Allana Kelly Cerqueira Lima Carvalho; Patrícia Ribeiro Feitosa Lima; José Airton Pontes Junior; Valter Cordeiro Barbosa Filho (O Mundo da Saúde)
Body Literacy (BL) is recognized by the World Health Organization as a key element in promoting a more active and healthy life. Technologies aimed at strengthening the competencies of School Physical Education (SPE) teachers to recognize this element in pedagogical practice are urgently needed. This study aimed to develop and validate an Educational Technology (ET) on the principles of BL within the pedagogical practice of SPE. This methodological study was grounded in the principles of Instructional Design and conducted in three phases: (1) analysis and planning (literature review), (2) development of the ET (didactic unit of a self-instructional teacher training course), and (3) content and appearance validation. In the final phase, 21 judges (9 researchers and 12 primary/ secondary school teachers) assessed the content and appearance of the ET using standardized instruments. Data analysis included the calculation of the Content Validity Index (CVI), Content Validity Ratio (CVR), and Appearance Validity Index (AVI). The developed ET comprises 17 pages, structured around three topics: School Physical Education as a promoter of health, the concept and principles of BL, and successful practical experiences. In the validation process, the ET achieved a total CVI of 0.98, a CVR of 0.75 for content, and an AVI of 0.95, indicating excellent validation indices. In conclusion, this ET may serve as a training resource for teachers on how BL can be incorporated into SPE pedagogical practices, contributing to holistic student development and health promotion in schools.